Deterrence of Radicalism through Multicultural Education among Students - Kurnia, Rina (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2022)
Students who are in the age range of 18 to 21 years are in their late teens. They have a high curiosity, one of which is on the spiritual aspect. They are looking for their true identity to define the right way of life according to the guidance of the Qur'an and As-Sunnah. Viewed from a social perspective, students come from various regions, ethnicities with different religious understanding and diverse social backgrounds, so multiculturalism is reflected in Bhineka Tunggal Ika. Thus, there is a potential for integrative and disintegrative values among students. Efforts to define the life meaning and identity that is not fortified by correct religious understanding and the influence of friendship based on disintegrative values can lead to radicalism. Therefore, the purpose of this research was to counteract the understanding of radicalism among students through multicultural education, so that the true meaning of life according to the guidance of the Al-Qur'an and As-Sunnah through integrative values can be internalized in thoughts and attitudes and manifested in actions. The research method used was descriptive qualitative. The results of the study show that there is increased understanding of the dangers of radicalism so that exclusive understanding of religious doctrines can be minimized and radicalism can be prevented through multicultural education.